(untitled) (New York, NY., 2002)
Behavioural ecotoxicology is an emerging field dealing with the effects of environmental pollutants on the behaviour of animals. Behavioural techniques derived from experimental psychology, behavioural pharmacology and neurotoxicology are applied to detect and characterise changes in animals living in the environment exposed to various pollutants. Behavioural effects are then interpreted in an ecological context considering the long-term relevance of these changes at both the individual and population level.
Keywords: Hành vi động vật,Ô nhiễm,Animal behavior,Pollution; Diện mạo môi trường,Environmental aspects